“People’s libraries” of the Society of zealots of Russian historical enlightenment at the turn of the 19th and 20th centuries - Jie Yu (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
At the beginning of the reign of Nicholas II, representatives of the conservativeoriented élite and their supporters from other social strata established the Society of Zealots of Russian Historical Enlightenment in memory of Emperor Alexander III with the aims of maintaining the ideological course of the Emperor (who died in 1894), as well as preventing the return to the reforms in the spirit of Alexander II. One of the directions of its activity was propaganda of political values of Alexander III among common people. For this purpose, in the late 1890s the society began to organise “people’s libraries”, where rural and urban residents could read the relevant ideological literature and where educational talks would be held with them within the ideological guidelines of the Society. The Society’s leadership was careful in deciding who among its members would be entrusted with the organisation of such libraries. To prevent the libraries from receiving ideologically undesirable literature, a complex centralised system of supplying them with both already published editions and new ones was developed. In the fi rst years of its implementation, before the political crisis of 1905–1906 and following liberal reforms, this project of the Society can generally be regarded as successful. An extensive network of libraries was established throughout Russia, and these librarians managed to handle the demands of their users. However, this stage witnessed a growing interest of readers in current events and the necessity to provide libraries with periodicals. Readers were mainly interested in fi ction and popular historical works, while spiritual literature was less asked for, except for the period of Lent. Later, during the liberalisation of the internal political life of the country, these trends could not but create diffi culties for libraries in terms of maintaining their ideological orientation.